2017
DOI: 10.18203/2349-2902.isj20170215
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between Mannheim peritonitis index and APACHE II in predicting the outcome in patients of peritonitis due to hollow viscous perforation

Abstract: Background: The identification and early assessment of peritonitis patient is often required in surgical emergency to select the high risk patients for intensive management for better outcome. This is a comparative study of efficacy between Mannheim peritonitis index and APACHE II in predicting the outcome in patients of peritonitis due to hollow viscous perforation.Methods: Comparative and prospective study in 50 patients of hollow viscous perforation admitted and operated in surgical emergency, Patna Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…9,10 According to Kumar et al, most common cause of perforation peritonitis was peptic ulcer perforation (36%) followed by typhoid ileal perforation (20%) followed by appendicular perforation (16%). 8 In present study highest incidence of SSI was seen in gastro duodenal perforations, 37.1% in control group and 20% in case group. There was a statistically significant reduction of SSI in the intervention group in case of duodenal and appendicular perforations at p<0.05.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…9,10 According to Kumar et al, most common cause of perforation peritonitis was peptic ulcer perforation (36%) followed by typhoid ileal perforation (20%) followed by appendicular perforation (16%). 8 In present study highest incidence of SSI was seen in gastro duodenal perforations, 37.1% in control group and 20% in case group. There was a statistically significant reduction of SSI in the intervention group in case of duodenal and appendicular perforations at p<0.05.…”
Section: Discussionsupporting
confidence: 49%
“…There was no significant statistical difference in the mean age of the patients in case and control group. 8,9 In present study patients in age group of 18-30 years had 12% incidence of wound infection in case group and 20% incidence in control group. Patients in age group of 51-60 years had 16% surgical site infection rate in case group and 28.6% in control group.…”
Section: Discussionsupporting
confidence: 45%
“…Rajendra Singh Jhobta et al (Kumar et al, 2017), in their study, observed 84% of males as the majority for Perforation Peritonitis. Similarly, Ranjan et al (2015) found 52% males and 48% females.…”
Section: Literature Reviewmentioning
confidence: 84%
“…For more precise risk stratification, surgeons should use both the APACHE II and MPI scores. 24 Several studies have shown that laparoscopic reintervention for colorectal anastomosis leaks is feasible and safe. 6,7,[25][26][27] Laparoscopic reintervention was recently added to the International Study Group of Rectal Cancer (ISREC) classification as a possible therapeutic alternative.…”
Section: Discussionmentioning
confidence: 99%